EFL Teacher Trainees’ Attitudes and Experiences Considering the Use of Digital Learning Games: A Survey-based Study - Rantanen, Aliisa (My University, 2022)
This Master’s thesis examined the attitudes and experiences that English as a Foreign Language (EFL) teacher trainees in Finland had about the use of digital learning games in L2 teaching and learning. ICT is nowadays largely utilized in school environments and the newest National Core Curriculum highlights its use as well. Game-based learning and gamification are popular trends in education and the creation of digital learning games that are purposefully designed for learning, is an expanding field. The aim of this thesis was to discover the respondents’ 1) attitudes, 2) practical experiences, and 3) level of ICT skills considering the use of digital learning games. The study material (N=74) consisted of a Webropol survey that was sent to all six Finnish universities that had English major and EFL teacher training programs in the fall of 2020. The survey had five sections and 39 questions. Both quantitative and qualitative methods were used in the analysis. The figures presented in the analysis were produced with the Webpropol 3.0. software. Based on the thesis’ research questions and the findings from the survey analysis, three main themes were discovered from the respondents’ answers (attitudes, experiences, ICT skills). These themes were then further discussed in the thesis. Based on the survey analysis, the EFL teacher trainees in Finland had highly positive attitudes towards the use of digital learning games. Over 75 percent of the respondents had also already used digital learning games when teaching English and had acquired positive experiences from their use. While the respondents’ thought that they could furthermore develop their ICT skills, 95 percent of them considered the level of their current skills to already be sufficient enough to use digital learning games in education. Future studies about the topic could, for example, focus more on the attitudes and development of comprehensive school pupils.
Keywords: Digital learning games, ICT in L2 education